Digital Marketing and Branding Training for MSME Products in Lumajang - Ayu Nareswari; Nur Latifa Isnaini Putri; Aji Prasetyo Suyono (TGO Journal of Community Development, 2024)
This activity aims to enable MSME actors in Lumajang to understand the importance of digital marketing as an effort to help promote their products through social media and product branding to create a distinctive feature of MSME products in Lumajang Regency. This training aims to improve MSME actors' understanding of digital marketing and product branding, as well as to help them utilize social media and e-commerce to expand market reach. The training method is in the form of presentations and interactive discussions that discuss the use of digital platforms. The results of the training showed an increase in MSME actors' understanding of the importance of digital marketing and product branding. Participants began to understand how to use social media to promote products effectively, reduce marketing costs, and increase competitiveness through a unique and memorable brand image. In conclusion, this training provides significant provisions for MSME to optimize the potential of technology in supporting business development.